2012
DOI: 10.1021/bc3004205
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Biofunctionalization of Polysilicon Barcodes for Adhesion to the Zona Pellucida of Mouse Embryos

Abstract: Cell tracking is an emergent area in nanobiotechnology, promising the study of individual cells or the identification of populations of cultured cells. In our approach, microtools designed for extracellular tagging are prepared, because using biofunctionalized polysilicon barcodes to tag cell membranes externally avoids the inconveniences of cell internalization. The crucial covalent biofunctionalization process determining the ultimate functionality was studied in order to find the optimum conditions to link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…WGA shows its highest affinity to N-acetyl-D-glucosamine and N-acetyl-D-neuraminic acid monosaccharides (Bhavanandan and Katlic, 1979), abundant in the ZP of most mammalian species (Skutelsky et al, 1994;Habermann et al, 2011). Next, the biofunctionalization of the polysilicon barcodes with the WGA lectin was optimized, and we found that barcodes with high surface roughness and covalently biofunctionalized using triethoxysilylundecanal (TESUD) as the linker offered excellent attachment and retention rates onto the mouse embryo ZP (Penon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…WGA shows its highest affinity to N-acetyl-D-glucosamine and N-acetyl-D-neuraminic acid monosaccharides (Bhavanandan and Katlic, 1979), abundant in the ZP of most mammalian species (Skutelsky et al, 1994;Habermann et al, 2011). Next, the biofunctionalization of the polysilicon barcodes with the WGA lectin was optimized, and we found that barcodes with high surface roughness and covalently biofunctionalized using triethoxysilylundecanal (TESUD) as the linker offered excellent attachment and retention rates onto the mouse embryo ZP (Penon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Embryos tagged with a single barcode were inspected every 24 h to assess the number of embryos that retained a barcode (retention rate). [16][17][18][19][20] For instance, just by adding 3 barcodes per embryo we can increase the retention rate up to 80% (in the case of the pushpin method). After the initial stage, the retention rate decreased following embryo development (Fig.…”
Section: The Barcode Retention On the Zpmentioning
confidence: 99%
“…However, some mismatching errors have been reported worldwide. 17 This lectin was demonstrated to chemically bind the polysilicon barcodes to the external surface of the ZP, which is rich in specific carbohydrates, avoiding direct contact between the barcodes and the embryo. Many different approaches from the fields of micro-and nanotechnologies have been proposed for cell labelling.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid materials obtained by the combination of micro-and nano-technology are considered as extremely relevant to science and technology, in particular for applications in biomedical science, catalysis and waste treatment [1][2][3]. Advances in micro-and nano-fabrication methods have provided new means of fabricating microand nano-devices for drug and gene delivery [4][5][6], tissue engineering [7], biosensors [8,9] and diagnostic systems, for proteins [8], DNA microarrays [10] and microfluidic circuits for biochemical sample preparation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years we have worked on (bio)chemical functionalization of microfabricated silicon-based microparticles and studied their applications in biology. We have reported on the adhesion of lectin-functionalized encoded microparticles to the zona pellucida of embryos for tagging purposes [8,9,14], on the internalization of silicon oxide microparticles in HeLa cells as intracellular pH sensors [36], as well as on the interaction of multimaterial microparticles with different types of cell lines [3]. We have also explored the phototoxicity of photosensitizer-functionalized iron oxide [37] and gold nanoparticles [38][39][40] as potential carriers of use in PDT [41].…”
Section: Introductionmentioning
confidence: 99%